Is Eating Fish Related-Psychiatric Disorders? A Case Report of Female Child with Schizopherinia Related Fish Ingestion (Global Journal of Medical Research, 2014)
Abstract not found
Keywords: knowledge; risk factors; vaccination; je; rupandehi